Tetramethylpyrazine and renal ischemia-reperfusion injury: a systematic review and meta-analysis of preclinical studies - Fu, Zhongmei; Jiang, Lianyan; Su, Xiaojuan; Wang, Hua; Li, Mingquan (Frontiers in Pharmacology, 2025)
ObjectivesThe aim of this systematic review and meta-analysis is to synthesize the effects and mechanisms of Tetramethylpyrazine (TMP) on renal outcomes in animal models of renal I/R injury.MethodsAnimal studies from seven electronic databases were searched up to October 2024. The risk of bias of the selected studies was assessed using the SYRCLE risk of bias tool. Standardized mean difference (SMD) or mean difference (MD) were estimated for the effects of TMP on serum creatinine (Scr), blood urea nitrogen (BUN), oxidative stress, inflammation and apoptotic. Random-effects models were used to summarize results. Heterogeneity was expressed as I2. Subgroup analyses were used to clarify the sources of heterogeneity. Egger’s test was used to assess publication bias. Sensitivity analyses were used to assess the robustness of the results. Statistical analysis was performed using RevMan 5.3 software.ResultsThirty studies involving 559 animals were identified for analysis. TMP treatment significantly decreased Scr (SMD = 2.35, 95% CI: −2.97 to −1.72, P < 0.05), BUN (SMD = −2.4, 95% CI: −3.01 to −1.79, P < 0.05). TMP treatment significantly improved oxidative stress expression (i.e., SOD, MDA, GSHPX, CAT, TAC) and alleviated inflammation levels (i.e., TNF-α, ICAM-1, IL-6, IL-10, NLRP3). TMP treatment also regulate the expression of apoptosis-related proteins (i.e., bcl-2, Bax, caspase 3, Caspase-12 and GRP78).ConclusionTMP could improve renal outcomes and alleviate injury through multiple signaling pathways. However, positive results should be treated with caution due to the significant heterogeneity and poor quality of the included studies.Systematic Review RegistrationCRD420251017081.